Construction of Thai Monosyllabic Word Lists for Speech Recognition Test of Adults - Mana, Paphawee; Yimtae, Kwanchanok; Thanawirattananit, Panida (Biomedical Sciences and Clinical Medicine, 2025)
Objective The objective of this study was to construct new Thai monosyllabic word lists that are phonetically balanced and to study the accuracy of speech recognition measuring tests for adults. Methods This study creation of four Thai monosyllabic word lists (KKU lists) of twenty-five words each in a CD recording based upon an accuracy evaluation. The 76 participants recruited were between 19 and 70 years of age and were recruited based on four groups of hearing level. Each group of 19 subjects consisted of people with normal hearing as well as people with moderate, moderately severe, and severe sensorineural hearing loss with symmetrical hearing. Only the dominant ear of each of the participants was chosen for testing. Audiometry in that ear was conducted using randomized nine-word lists from the four newly constructed Khon Kaen University lists (KKU lists) and five lists of RAMA SD lists-1 from the original Thai monosyllabic word lists (OTL) [OTL consisted of RAMA SD list-1 (there are 5 lists) and RAMA SD list-2 (there are 4 lists)]. The participant’s accurately spoken words will be recorded as a number and percentage. Results No statistically significant differences were found in the speech recognition scores of any of the four KKU lists among the four participant groups (p > 0.05). Similar to Kasmer and Brown’s study, the speech recognition scores (SRS) of the KKU lists and OTL lists declined as the degree of the severity of hearing loss increased. The score range (min-max) at each level of hearing loss for all nine-word lists was in the standard value range. However, the SRS of the KKU lists were found to be closer to the standard reference than the scores from the OTL list. Conclusions The KKU lists can provide more accurate score results and more precise diagnoses of hearing loss and can also be applied in clinical examination and speech recognition testing.